Biological traits suggest a niche overlap between two grapsid crabs sharing the rocky intertidal of the eastern Mediterranean. (8th July 2015) - Arab, A.; Kazanjian, G.; Bariche, M.
Abstract : The current study investigated basic biological features for two co-occurring shore crabs Pachygrapsus marmoratus and P. transversus in the eastern Mediterranean Sea. Differences in population structure, reproductive periods and settlement patterns were studied along the coast of Lebanon. Sizes of sampled individuals ranged from 4 to 37 mm carapace width (CW) for P. marmoratus and from 3.5 to 24 mm CW for P. transversus . Males were larger than females in both species, each of them exhibiting different size frequency distributions. Both male and female proportions were similar for P. marmoratus while males dominated the population of P. transversus . Fecundity and egg sizes were higher in P. marmoratus and fecundity was directly related to body size for the two crabs. Size structures differed between studied locations showing size restrictions for specific size-classes. Females from both species remained ovigerous for about 5 months, with P. transversus (May–August) started 1 month after P. marmoratus . Larger sized females displayed higher fecundities. The recruitment of juveniles lasted 5 months for both P. marmoratus (December–May) and P. transversus (November–April). Our results showed that niche partitioning occurred between the two species, where P. marmoratus starts incubating earlier than P. transversus while young of the year of the latter settle earlier on the reefs, taking advantage of convenient seawater temperatures and thus minimizing competition. This study shed some light on the populations of grapsid crabs living in the eastern Mediterranean and provided baseline information on the biology and ecology of the two congeneric shore crabs and their interactions.